### Table of Contents

## Moufang loops

Abbreviation: **MLoop**

### Definition

A \emph{Moufang loop} is a loops $\mathbf{A}=\langle A,\cdot ,\backslash,/,e\rangle $ such that

$((xy)z)x = x(y(zx))$, $y(x(yz)) = ((yx)y)z$, $(yx)(zy) = (y(xz))y$

Remark:

##### Morphisms

Let $\mathbf{A}$ and $\mathbf{B}$ be Moufang loops. A morphism from $\mathbf{A}$ to $\mathbf{B}$ is a function $h:A\rightarrow B$ that is a homomorphism:

$h(xy)=h(x)h(y)$, $h(x\backslash y)=h(x)\backslash h(y)$, $h(x/y)=h(x)/h(y)$, $h(e)=e$

### Examples

Example 1:

### Basic results

### Properties

### Finite members

$\begin{array}{lr}
f(1)= &1

f(2)= &

f(3)= &

f(4)= &

f(5)= &

f(6)= &

f(7)= &

\end{array}$